Educación para la ciudadanía y la convivencia - Ascensión Palomares Ruiz (Universidad de La Rioja, 2013)
Education can be basically considered as the consolidation of a set of values which are essential in the life of a person right inside the society where they have to get integrated. It acquires a great transcendence in this crisis times, in which certain generic values and even technological advance are imposing themselves over what is specifically human, so it is necessary to develop new attitudes which lead to a new kind of culture, which sets us free from dehumanization and encourages the fight for the collective interests, and favours them over the individual or partial ones. In the field of education, every professional must be aware of the fact that their task transcends the mere communication of some curricular contents and must reach meaningful concepts and aim to the awakening of participative behaviour in the construction of the surrounding society. We are facing a social problem which requires a holistic treatment, in which our public representatives -and this include trades- should change their attitudes first. We should not forget the fact that most pupils showing aggressive behaviour become violent adults. Therefore, education for peace, tolerance and solidarity from the youngest age, are the best way to prevent these situations and also the worrying domestic violence. This is a task in which everyone, not only parents and teachers, but the whole society, should work in cooperation.